Proses Berpikir Aljabar Siswa SMP Ditinjau Dari Kemampuan Akademik Matematika Dan Gender - Ridha Chairunisa; Maimunah Maimunah; Yenita Roza (Universitas Kanjuruhan Malang, 2020)
The purpose of this research is to know algebra thinking process of students in rectangular material reviewed from Mathematics ability and gender. The method of this research was qualitative descriptive. The research subjects were 9 female students and 9 male students of grade IX with high, medium, and low Mathematics ability. The research instruments were test and interview. The research results show that female students with high ability have algebra thinking. Male students with high ability have algebra thinking but indicator of concluding and rechecking was not fulfilled yet. Female students with medium ability have algebra thinking but there was carelessness in the calculation. Male students with medium ability have started to thought algebra but at indicator of interpreting and applying Mathematics findings was not fulfilled yet. Female and male students with low ability do not think algebra yet because all indicators were not fulfilled. This occurred because they still did not understand algebra concept until they could not solve Mathematics problem. Female and male students with high and medium ability who already thought algebra can solve Mathematics problem. However, female and male students with low ability still do not think algebra until they cannot solve the problem.